Determinação do tempo do trânsito gastrointestinal em Podocnemis expansa Schweigger, 1812 (Tartaruga-da-Amazônia) (Testudines, Podocnemididae) - Lopes, Lino Antonio Raimundo (2006)
The amazon turtle hás herb-based diet, but it can be fed with a small quantity of animal-based food. Digestion speede of these animals is influenced by both temperature and nutricion status. To understand the digestion process of food in animal organisms, studies on the gastrointestinal tract transit are necessary. The objective of this study was to determine the gastrointestinal transit time of this reptile, in order to supply information to clinical and surgery operations. Ten animals from Nova Crixás - GO, Brasil with approximately 2.5 years of age e 1.5 kg of weight were sampled. The animals were orally fed with a barium sulfate suspension (Bariogel®) at 10ml/kg mixed with mineral oil (Nujol®), at a rate of 70% of barium sulfate for 30% of mineral oil. Afterwards, the animals underwent radiography in a dorsum ventriloquoal position, with the X-ray device adjusted at 80 Kv and 250 mA, in time intervals as to follow the permanency of contrast in the organism. Five minutes after the contrast was supplied, the stomach was fulfilled. The duodenal, ileum and jejunum segments were completely filled between 6 and 24 hours, cecum between 24 hours an 4 days and colorectal between 24 hours and 5 days. The stomach was free from between 5 and 24 days. The contrast elimination from the duodenal segment happened between 7 and 15 days and from the jejunumileum segments between 7 and 17 days. The cecum was partially free from contrast between 12 and 29 days, but was completely free between 15 and days. So, mean gastrointestinal transit time in this group of P. expansa was 22.5, with a maximal value of 29 days and a minimal of 15 days.